Acceptability of HIV self-testing in African students: a cross-sectional survey in the Democratic Republic of Congo - Tonen-Wolyec, Serge (Pan Afr Med J, 2019)
INTRODUCTION: The empowerment of young people aged 15-24 years is a key component of an effective AIDS response. HIV self-testing (HIVST) is progressively being implemented in the Democratic Republic of Congo (DRC). METHODS: Socio-demographic and behavioural factors associated with acceptability of HIVST were evaluated among university students in Bunia, DRC. A representative cross-sectional study was conducted using a self-administered semi-structured questionnaire. RESULTS: A total of 1,012 students were recruited. Acceptability of unsupervised HIVST was higher in the group of young students as compared with older students and was markedly associated with prior knowledge on HIVST. CONCLUSION: Adapted communication about HIVST appears likely essential to increase the supply and use of HIVST among students in DRC.